2015
DOI: 10.4236/jep.2015.67069
|View full text |Cite
|
Sign up to set email alerts
|

Organic Manures and Crop Residues as Fertilizer Substitutes: Impact on Nitrous Oxide Emission, Plant Growth and Grain Yield in Pre-Monsoon Rice Cropping System

Abstract: It has been previously argued that application of organic residues added in soils has a great impact on soil quality, grain productivity as well as greenhouse gas emissions. Substitution of chemical fertilizers has become a common practice in agricultural systems which consequently affect the greenhouse gas emissions from agricultural fields. To observe the effects of organic manures and crop residues amendments, five fertilizer treatments including conventional inorganic nitrogen fertilizer-NPK, cow manure, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…There was an increase of N 2 O emissions from the organic fertiliser treatments (CM at Site 1) with respect to the control, (Table 5), but higher the larger the organic-C applied with the organic fertiliser ( Table 3). The results of the present study are in agreement with those of Das and Adhya (2014) and Baruah and Baruah (2015), who reported a similar trend when chicken manure was applied to paddy fields. For the other treatments, the low soil organic matter content (2.2% at Site 1 and 1.0% at Site 2) could have been a limiting factor for denitrification in the control and mineral treatments, and with the low PS dose at Site 2 due to its low organic matter content (Table 3).…”
Section: Nitrous Oxide Emissions During the Rice Cropsupporting
confidence: 93%
“…There was an increase of N 2 O emissions from the organic fertiliser treatments (CM at Site 1) with respect to the control, (Table 5), but higher the larger the organic-C applied with the organic fertiliser ( Table 3). The results of the present study are in agreement with those of Das and Adhya (2014) and Baruah and Baruah (2015), who reported a similar trend when chicken manure was applied to paddy fields. For the other treatments, the low soil organic matter content (2.2% at Site 1 and 1.0% at Site 2) could have been a limiting factor for denitrification in the control and mineral treatments, and with the low PS dose at Site 2 due to its low organic matter content (Table 3).…”
Section: Nitrous Oxide Emissions During the Rice Cropsupporting
confidence: 93%
“…The critical temperature which can limit composting is yet to be defined [33], however, Barua and Baruah [34] suggested that a temperature of 55°C -60°C should be maintained for up to three days for efficient composting.…”
Section: Resultsmentioning
confidence: 99%
“…As the addition of organic materials to soil channels the accumulation of extra carbon (Bharali et al 2017;Baruah and Baruah 2015;Kirkby et al 2013), SOC was found enhanced under T3, T5 and T6, i.e., under the inorganic fertilizer blended with organic materials. The increased SOC helps microbes to provide nutrients to plants by keeping carbon and nitrogen balanced in soil, otherwise microbes would decompose existing organic carbon of the soil (Fontaine et al 2004;Murphy et al 2015;Poeplau et al 2017).…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Such fertilizers provide essential nutrients to soil, and also improve other soil properties, such as water-holding capacity, nutrient-holding capacity and microbial activity of soil. However, a huge volume of organic fertilizer is required for achieving potential of high yielding rice varieties, which will directly step up the cost of farming (Baruah and Baruah 2015; Baruah et al 2016). In addition, the decomposition of an organic matter under humid tropical condition is relatively hasty and its gathering is minimal in upland irrigated soils.…”
Section: Introductionmentioning
confidence: 99%